Synthesis and Characterization of ZnO-Doped CuO with the Addition of Monoethanolamine Using the Sol-Gel Method - Nazellia Asnur; Hary Sanjaya; Indang Dewata; Fajri Ikhsan (Darul Yasin Al Sys, 2026)
Semiconductors are materials capable of conducting electricity within specific limits, a property that is essential for applications in photocatalysts and solar cells. Copper oxide (CuO), a transition metal oxide, exhibits favorable properties as a p-type semiconductor and is characterized by a narrow bandgap ranging from 1.2 to 1.8 eV. However, CuO has a limitation in the form of a high electron–hole recombination rate, which requires modification through doping and additive incorporation. This study aims to analyze the effects of zinc oxide (ZnO) doping and the addition of monoethanolamine (MEA) on the characteristics of CuO nanoparticles synthesized using the sol–gel method. This method was selected because it can produce materials with a large surface area and good stability. Characterization was conducted using ultraviolet–diffuse reflectance spectroscopy (UV–DRS) to determine bandgap energy. The findings show that the optimal bandgap value was obtained at 20% ZnO concentration, with a bandgap energy of 1.33 eV, while the addition of 2 mL MEA produced a bandgap energy of 1.42 eV. The decrease in bandgap value indicates that ZnO doping affects the optical properties of CuO. A smaller bandgap narrows the distance between the valence band and the conduction band, thereby facilitating electron excitation and requiring lower photon energy. This study contributes to the development of modified CuO-based semiconductor materials by demonstrating the potential role of ZnO doping and MEA addition in improving optical characteristics relevant to photocatalytic and solar cell applications.